Perancangan Iklan TVC Perumahan Cerme Square Residence dengan Teknik Animasi 3D Sebagai Upaya Meningkatkan Brand Awareness - Prayoga, Al Lukman Arif; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The purpose of the design of the housing TVC advertising Cerme Square Residence is to raise awareness and facilitate the community to do its needs. This research was conducted with qualitative research methods that will conduct interviews, observation, documentation, and literacy to formulate the concept of advertising TVC. Analysis of data using multiple stages, namely data reduction, data presentation, and conclusion. After the data is analyzed, it was found the design concept or keyword of TVC advertising design of "Lives". Description of "Lives" is the existence of a life in the region Cerme Square Residence. The concept of "Lives" is due to appear before the media campaign that does not have a concept or do not have a uniform concept that causes the level of awareness is low. The concept of "Lives", aims to create an area that has a life, activities and events. That is, the concept of "Lives" expected to be an area of Cerme Square Residence that allows people to carry out their activities. Which means with the area surrounding communities Cerme Square Residence Cerme no longer have to  go  far  to  the  center  of  Gresik.  For  the  concept  of  "Lives"  provides  an  overview of  the  community convenience gained around Cerme and help increase brand awareness. Keyword : Iklan TVC, Animasi 3D, Perumahan, Cerme Square Residence